Application of the Problem-Based Learning Model In The Course Of Automation Of Public Relations Management And Protocols in the OTKP Department at State Vocational High School 7 Makassar - Nurul Faisah Andriani; Muh. Darwis; Jamaluddin Jamaluddin (ASHA Publishing, 2026)
This study aims to determine how the application of the problem-based learning model in the subject of automation of public relations and protocol management of the OTKP department at SMK Negeri 7 Makassar. The type of research used in this study is a qualitative descriptive type of research and the data collection techniques used are observation, interview, and documentation techniques with 5 informants, namely three teachers of the subject of automation of public relations and protocol management of the OTKP department, and two students of class XII OTKP at SMK Negeri 7 Makassar. The results of the study, observations and interviews can be concluded that the Problem Based Learning learning model in the public relations and protocol subjects of the OTKP department at SMK Negeri 7 Makassar was implemented effectively. It can be seen at the stage of student orientation to the problem in the Problem Based Learning learning model applied by the teacher in the classroom by providing an explanation of the learning material and the teacher introducing an interesting problem to students in the public relations and protocol activities material, then the teacher provides examples of problems through learning videos on the internet such as YouTube. From the stage of organizing students to learn in class, the teacher applies the problem based learning model by dividing students into small groups, each consisting of 6-7 people per group to make it easier for students to identify the problems given by the teacher. At the stage of guiding individual/group experiences of students, at SMK Negeri 7 Makassar the teacher provides motivation by guiding students who have difficulty in group discussions, in this case the teacher ensures that students understand the special learning material for public relations and protocol activities as in the learning implementation plan. At the stage of Developing and presenting the results of the work, the teacher helps students in planning and preparing work or assignments that are in accordance with the material of public relations and protocol activities by developing assignments in the form of group discussions, presenting work in the form of group presentations. And at the stage of analyzing and evaluating the problem-solving process, after students have made their presentations they will analyze questions from other groups to find answers and then will be given an evaluation by the teacher in oral form such as question and answer questions.